2005
DOI: 10.1088/0957-4484/16/9/025
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal growth of metallic nanowires with preferred orientation

Abstract: Single-crystalline metallic nanowires, Ni, Ag, and Zn, were successfully fabricated using an anodic aluminium oxide (AAO) template by electro-deposition. The single-crystalline Ni and Ag nanowires showed face-centred cubic (fcc) structure with a preferred orientation along the [220] direction. Zn nanowires with hexagonal close-packed (hcp) structure also had preferred orientation along [220]. The structure of metallic nanowires depended on the deposition conditions and can be controlled by the conditions. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
88
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 23 publications
7
88
0
Order By: Relevance
“…Moreover, researchers have experimentally found that FCC metal NWs prefer to grow along the <110>, and not <100> axial direction, as previously reported for Au 25 , Ni 26 , Ag 27,28 , Cu 29 and Pd NWs 30 . Finally, most experimental studies of NW mechanical properties have been performed on non-<100> orientated NWs 18,[31][32][33][34] .…”
supporting
confidence: 61%
“…Moreover, researchers have experimentally found that FCC metal NWs prefer to grow along the <110>, and not <100> axial direction, as previously reported for Au 25 , Ni 26 , Ag 27,28 , Cu 29 and Pd NWs 30 . Finally, most experimental studies of NW mechanical properties have been performed on non-<100> orientated NWs 18,[31][32][33][34] .…”
supporting
confidence: 61%
“…The mechanisms for the effect of applied potential and pH value on the grain size, texture and magnetic properties of Ni nanowire arrays have been discussed. Electrodepositing elements into anodic alumina oxide (AAO) templates provides a simple technique to obtain the highly ordered nanowire arrays [1][2][3]. The low-cost AAO films are thermally stable at high temperature and the pore channels they contain are of uniform size, parallel to each other and perpendicular to the film surface.…”
mentioning
confidence: 99%
“…It has also been found that the AAO template is an ideal template because it has many desirable characteristics, including tunable pore dimensions over a wide range of diameters and lengths, good mechanical strength and thermal stability. Among the well-developed fabrication methods based on AAO template, electrodeposition is recognized as one of the most efficient methods in controlling the growth of nanowires and has been widely used to produce a variety of metal [9,10], semiconductor, and conductive polymer nanowire arrays.…”
Section: Introductionmentioning
confidence: 99%